HyperDesign : 6th Shanghai Biennale 2006. - Zengxian, Fang; Jiang, Xu; Shanghai Biennale Shanghai 2006 (Shanghai : Shanghai Biennale, 2006)
Op de Beeck, Hans ; Wenling, Chen ; U-Ram, Choe ; Choi, Cody ; Craig-Martin, Michael ; Deleu, Luc ; Dejanoff, Plamen ; Demand, Thomas ; Pardo, Jorge ; De Nijsthe, Marnix ; Yong-Seok, Oh ; Nishijima, Haruki ; Opie, Julie ; et al.
Shanghai Biennale, September 6 - November 5, 2006
kunstcatalogus